Problems of creating scientific and methodological bases of spent nuclear fuel dry cask storage thermal safety in Ukraine - Alyokhina, S.V. (Проблеми машинобудування, 2018)
An analytical review of modern researches into spent nuclear fuel (SNF) dry cask storage, or dry storage thermal processes is presented and problems of creating scientific and methodological foundations for SNF dry storage thermal safety are discussed. Подано аналітичний огляд сучасних досліджень теплових процесів за сухого зберігання відпрацьованого ядерного палива (ВЯП) та висвітлено проблеми створення науково-методологічних основ теплової безпеки сухих сховищ відпрацьованого ядерного палива. Представлен аналитический обзор современных исследований тепловых процессов при сухом хранении отработавшего ядерного топлива (ОЯТ) и освещены проблемы создания научно-методологических основ тепловой безопасности сухих хранилищ отработавшего ядерного топлива.